Distinct Factors Associated With Better Self-care in Heart Failure Patients With and Without Mild Cognitive Impairment. Issue 6 (November 2019) - Lee, Kyoung Suk; Choi, Jin-Oh; Jeon, Eun-Seok; Park, Jae-Hyeong; Jung, Mi Sook; Lee, Zian; Lee, Hyeong Suk; Yoo, Hye Jin
Abstract : Background: A decline in cognition may limit patients' ability to effectively engage in self-care in those with heart failure (HF). However, several studies have shown no difference in self-care between HF patients with and without cognitive impairment. This may indicate that there are more salient factors associated with self-care in HF patients with cognitive impairment compared with those without cognitive impairment. Objective: The aim of this study was to explore which factors are related to self-care based on the presence and absence of mild cognitive impairment (MCI) among patients with HF. Methods: Patients with HF were recruited from outpatient settings. The Montreal Cognitive Assessment was used to screen for MCI. Self-care was measured with the Self-care of HF Index v.6.2. Two separate stepwise linear regressions were performed to identify which factors (HF knowledge, perceived control, functional status, multimorbidity, executive function, and social support) predicted self-care in HF patients with and without MCI. Results: Of the 132 patients in this study, 36 (27.3%) had MCI. Self-care maintenance and management were associated with social support (β = 0.489) and executive function (β = 0.484), respectively, in patients with MCI. Perceived control was associated with both self-care maintenance and management in patients without MCI (βs = 0.404 and 0.262, respectively). Conclusion: We found that social support and executive function were associated with self-care in HF patients with MCI, whereas perceived control was associated with self-care in HF patients with intact cognition. Clinicians should develop tailored interventions to enhance self-care by considering the distinct factors associated with self-care based on the presence or absence of MCI.